Long-term outcome of paroxysmal atrial fibrillation catheter ablation with and without pulmonary vein dormant conduction after adenosine challenge - Skála, Tomáš; Přeček, Jan; Hutyra, Martin; Moravec, Ondřej; Tüdös, Zbyněk; Skálová, Jitka; Klementová, Olga; Antonická, Andrea; Zapletalová, Jana; Táborský, Miloš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
OBJECTIVES: The prognostic significance of adenosine-mediated pulmonary vein (PV) dormant conduction is unclear. We prospectively followed patients with adenosine-mediated PV reconduction with a subsequent repeated ablation until there was no reconduction inducible with patients without reconduction after PV isolation. METHOD AND RESULTS: Consecutive patients (n=179) with paroxysmal atrial fibrillation (AF) without prior catheter ablation (CA) were enlisted in the study. We used a point-by-point CA and general anesthesia in all patients. Twenty minutes after PV isolation we administered adenosine in a dose sufficient to produce an atrioventricular block. If a dormant conduction was present (n=54) we performed additional ablation until there was no adenosine mediated reconduction inducible. During 36 months of follow-up, all patients were examined for eight 7-day ECG recordings. There was no difference in arrhythmia recurrence rate between patients with and without dormant conduction (29.6 vs. 24.8% at 12 months, P=0.500; 31.5 vs. 30.4% at 36 months, P=1.000), for any echocardiographic parameter or any parameter of the ablation procedure. CONCLUSION: The patients with dormant conduction after adenosine during catheter ablation of paroxysmal atrial fibrillation with complete elimination of the dormant conduction by additional extensive ablation have the same outcome in the long term as patients without a dormant conduction.
Keywords: Pulmonary Veins; prognóza; Atrial Fibrillation; Recurrence; výsledek terapie; antiarytmika; venae pulmonales; katetrizační ablace; recidiva; Prognosis; Anti-Arrhythmia Agents; adenosin; Humans; lidé; Treatment Outcome; Catheter Ablation; fibrilace síní; Adenosine